A comparative study of adenoidectomy by microdebrider vs conventional method - Muniraju, M.; Saifulla, Mohammed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Adenoidectomy is a commonly performed ENT surgery. This present article aims to evaluate endoscopic powered adenoidectomy as an alternative for conventional curettage method. Methods: Sixty consecutive cases requiring adenoidectomy were randomized into two groups of thirty each. Group A underwent endoscopic assisted micro-debrider adenoidectomy and Group B underwent conventional adenoidectomy using the curettage method in study period from November 2015 to May 2017. Results: The average time taken in Group A was 34.10 minutes and in Group B was 22.83 minutes (p<0.001). The average blood loss in Group A was 29.57 ml as compared to 16.67 ml in Group B (p<0.001). The resection was invariably complete in Group A whereas five (16.7%) cases had more than 50% residual adenoid tissue in Group B. Four cases in group B had collateral damage whereas in Group A, there were no added injuries. Post operative pain was studied only in cases undergoing adenoidectomy alone. Group A (n=8) demonstrated a pain score of 3.50 – 3.09 whereas Group B (n=11) demonstrated a pain score of 2.75-2.55. In group A, the mean recovery period was 2.80 days and 8.23 days in Group B (p<0.001). Conclusions: Endoscopic powered adenoidectomy was found to be a safe and effective tool for adenoidectomy. The study parameters where endoscopic powered adenoidectomy fared better were completeness of resection, accurate resection under vision, lesser collateral damage and faster recovery time. On the other hand, conventional adenoidectomy scored in matter of lesser operative time and intra-operative bleeding.